A qualitative exploration of the perceived factors that influence alcohol consumption among South African girls and young women (AFYW) and the relationship with sexual risk behaviour - Grant, Jamie (Department of Public Health and Family Medicine, 2024)
South Africa (SA) has one of the highest rates of problematic alcohol consumption, with rates particularly concerning among young people. SA adolescent girls and young women (AGYW), from low-resourced settings, exhibit increasingly problematic alcohol consumption behaviours. As alcohol is a key determinant of sexual risk behaviours, it increases AGYW's already disproportionate burden of potentially negative sexual and reproductive health outcomes. This paper reports on analysis of qualitative data from interviews with AGYW and stakeholders, conducted in six SA provinces. Data were thematically analysed to explore respondent's perceptions of factors influencing AGYW's alcohol consumption and experiences of alcohol-induced sexual risk behaviour. Reasons for alcohol consumption included AGYW's desires for pleasure and enhanced sociability, but also to suppress negative emotions. Access to alcohol and social modelling were also perceived as influential factors. Alcohol consumption increased sexual risk through condomless sex and risk of sexual and physical violence against AGYW. Findings indicate that AGYW face negative social reactions to their consumption habits because they contradict social norms of youth and femininity. An understanding of motivations for alcohol use among AGYW, and the influence of the social environments, are useful for formulating alcohol risk-reduction strategies for AGYW and the communities in which they live.